Life cycle analysis of biowaste-to- biogas/biomethane processes: Cost and environmental assessment of four different biowaste scenarios organic fraction of municipal solid waste and secondary sewage sludge - Wang, Shuaibing; Lin, Haitao; Abed, Azher M; Mahariq, Ibrahim; Ayed, Hamdi; Mouldi, Abir; Lin, Zhixiang (Energy (Oxford), 2024)
Biowaste-to-biogas processes have been introduced to design a valuable and green renewable plant to achieve a sustainable society and environment. The biomethane production process through biogas upgrading instead of designing a combined heat and power (CHP) system can be more attractive. This study presents a life cycle analysis (LCA) from both cost and environmental standpoints for four biowaste-to-biogas/biomethane process scenarios. Biogas production is achieved through anaerobic co-digestion of the organic fraction of municipal solid waste (OF-MSW) and secondary sewage sludge (S-SS), incorporating a pre-treatment process based on the dark co-fermentation process (DCFP). Each scenario offers distinct methods for utilizing the hydrogen-rich gas and biogas, with varying degrees of energy recovery and efficiency. Two sensitivity studies were conducted under various utilizations of the recovered biomethane and the anticipated electricity mix. Scenario SC-1 (CHP-from-biogas) was found to be the most co-friendly favorable in eight out of eleven impact categories (under the CML/IA technique). Further, biogas upgrading-integrated options exhibited lower impacts. Replacing biomethane instead of petrol in scenarios with upgraded biogas was identified as the most effective approach against climate change. Financial analysis indicated that all layouts are economically viable, each demonstrating a positive NPV over a 20-year period (up to $11.57 million).